2000
DOI: 10.1161/01.cir.102.9.1007
|View full text |Cite
|
Sign up to set email alerts
|

Oxidant Stress and Aspirin-Insensitive Thromboxane Biosynthesis in Severe Unstable Angina

Abstract: These findings establish a putative biochemical link between increased oxidant stress and aspirin-insensitive TX biosynthesis in patients with unstable angina and provide a rationale for dose-finding studies of antioxidants in this setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
106
0
4

Year Published

2002
2002
2008
2008

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 204 publications
(121 citation statements)
references
References 38 publications
10
106
0
4
Order By: Relevance
“…Here we confirm the increase in F 2 -isoprostane excretion previously documented in hypercholesterolemia, 23,24 as well as in other conditions characterized by enhanced lipid peroxidation, such as type 2 diabetes, 20 unstable angina, 32 or heavy smoking. 21,22 Concomitant with the expected reductions in lipid levels, simvastatin reduced the elevated levels of 8-iso-PGF 2␣ by approximately one third, to levels found in healthy individuals, 20,21 mild smokers who were healthy, 22,25 or subjects with stable coronary artery disease.…”
Section: Discussionsupporting
confidence: 91%
“…Here we confirm the increase in F 2 -isoprostane excretion previously documented in hypercholesterolemia, 23,24 as well as in other conditions characterized by enhanced lipid peroxidation, such as type 2 diabetes, 20 unstable angina, 32 or heavy smoking. 21,22 Concomitant with the expected reductions in lipid levels, simvastatin reduced the elevated levels of 8-iso-PGF 2␣ by approximately one third, to levels found in healthy individuals, 20,21 mild smokers who were healthy, 22,25 or subjects with stable coronary artery disease.…”
Section: Discussionsupporting
confidence: 91%
“…On the other hand, it is also known that the plaque itself could release, once activated, biochemical substances such as, for instance, pro-oxidants, 26 -28 which, in turn, can stimulate the apoptotic process. 29 -31 The already accepted association between oxidative stress and ACS 32 together with the present finding that coincubation with Trolox markedly reduced the proapoptotic effect of serum would support this hypothesis.…”
Section: Original Findingssupporting
confidence: 64%
“…These findings suggested that there is a close relation between CAD and oxidative stress. In addition, the results are in agreement with previous studies (28,29) and demonstrate that coronary atherosclerosis may be associated with increased oxidative stress. The mechanisms responsible for the association between CAD and oxidative stress are unknown.…”
Section: Discussionsupporting
confidence: 92%